The Contact Point of Customary Law and Islamic Law (Legal History Perspective) - Sulistyarini, Rachmi; Budiono, A. Rachmad; Winarno, Bambang; Koeswahyono, Imam (International Journal of Social Sciences and Management, 2018)
The period before various legal traditions encounter to Indonesia, the people living in these islands has owned rules that contain the value of values as the original law. The term of original law is also known as the name of "chthonic" law, and is used as the customary law of the community of Indonesia, or the archipelago known at that time. The customary law tradition is very different from other legal traditions; this system has a special character that is very different from the character of other legal traditions. Furthermore, around the seventh century of AD, the influence of religion encounter as well; the first is Hinduism, then the religion of Islam brought by traders from Arabia and India. The term known as custom, with its unwritten form and religious element as the definition proposed by Soepomo (1996), is indeed identical with the term given by experts in the colonial period such as: “Godsdientige Wetten, Volks instelingen En Gebruiken" (Regulation of Religious Ordinance, People's Institution and Customs), "Godsdientige Wetten, Instelingen En Gebruiken (Religious Regulations, Institutions, and Customs), Met Hunne Godsdiensten en Gewoonten Samenhangen de Rechts Regelen" (Rules of law relating to Religion and religion customs habits), in addition there are also called the Islamic Law or Mohameden Law. It shows that at that time Customary Law is equalized as religious law. The point of contact between the two can also be identified from the theories that develop at that time as in the theory of Receptio in Complexu (Salmon Keyzer and van Den Berg); Receptie Theory (Scouck Hurgronye); Theory of Receptio a Contrario (Ha zairin). The relationship between customary law and Islamic law is widely found in the field of family law that is the issue of marriage law and inheritance law. After Independence, legislation products related to Islamic law include Law no 1 of 1974, Law no 50 of 2009, Law no 21 of 2008 regarding Islamic Banking. Int. J. Soc. Sc. Manage. Vol. 5, Issue-2: 51-59